Indian philosophical foundations of spirituality at the end of life. (2nd October 2018) - Inbadas, Hamilton
Abstract: Growing understanding of spirituality at the end of life demands more theoretical research on the subject. Empirical studies have highlighted the need for exploring philosophical and cultural concepts to facilitate a fuller understanding of spirituality at the end of life. This paper explores Indian philosophy to inform the conceptualisation of spirituality at the end of life in the Indian context. Three key themes from discourses on spirituality at the end of life have been analysed: the concept of the human person, the purpose of life and the meaning of death. The human person is from and of the Divine, eternal and is capable of cognition and experience. The purpose of human life is to unite with the ultimate Reality, the Divine, by living life righteously according to prescribed ways and by achieving detachment from the illusion of the world. Death is part of life and not that which ends it. The moment of death is an opportunity for the ultimate transformation, Moksha. Analysing these philosophical foundations can provide the contextual frame for understanding the spiritual needs of palliative care patients and their families and the possibility of developing culturally relevant approaches to providing spiritual care at the end of life.